Teacher's Strategy in Developing Practical Values of the 5th Pancasila Precepts in Thematic Learning in Elementary School - Aldila, Febri Tia; Rini, Endah Febri Setiya (Journal of Basic Education Research, 2023)
Purpose of the study: This study aims to find out and describe the strategies that teachers can use to develop the practical value of the five Pancasila precepts in the thematic learning process for first grade students at elementary school 36/I Kilangan. Methodology: This research is a qualitative research with a phenomenological approach. The samples in this study were school principals, teachers, and 2 low grade students at elementary school 36/I Kilangan. Collecting data in this study using observation sheets, interview guide instruments. in this study using the Miles and Huberman analysis technique. Main Findings: The teacher's strategy in instilling the practical values of Pancasila, especially the precepts "Social Justice for All Indonesian People" in thematic learning in class I elementary school 36/I Kilangan shows that the teacher has become a good role model for students, especially in applying a family attitude, balancing rights and obligations , as well as work hard. The teacher uses several strategies in its implementation. Novelty/Originality of this study: The novelty of this study is knowing the teacher's strategy in instilling the practical values of the Pancasila precept "Social Justice for All Indonesian People" in thematic learning at elementary school 36/I Kilangan. Teachers use character-based learning strategies such as the PAIKEM strategy, cooperative learning and inquiry, as well as various lectures to familiarize students with always reading and discussing.